STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS VI DI MI SALAFIYAH SYAFI’IYAH SEBLAK JOMBANG TAHUN AJARAN 2023/2024 - Asvi Mardana; Ali Mahsun (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research has a goal, namely that in the world of education a teacher is expected to be able to have teaching skills and strategies which aim to ensure that students are able to follow and absorb teaching material easily and well, especially in the ability to read the Qur'an. The method used in this research is qualitative and uses data collection techniques, namely: observation, interviews and documentation. Then the data that has been collected is then analyzed using three stages, namely: data reduction, presentation of the final data with conclusions. Informants in this research included the principal, head of curriculum, class teacher and students. The meeting point in this research focuses on a teacher's strategy in implementing Al-Qur'an learning which is related to students' ability to read it. In the world of education at MI, the most basic thing is that students are able to understand religious knowledge well. This is a common thing in MI schools. In this case, at least students are able to read the Koran fluently and memorize several letters in the reading. -reading prayers, because this is included in the teachings of the Islamic religion which are always used in everyday life. The conclusion of this research is that at MI Salafiyah Syafi'iyah, students in their learning use the sorogan method together in learning the Al-Qur'an and modern recitation material with the aim of students being able to understand the material easily.